Environmental Strategy and Environmental Management Accounting as Contributors to Environmental and Financial Performance: The Case of Manufacturing Firms in Vietnam for the Sustainable Development Goals (SDGs) - Khanh , Thai Hong Thuy; Rajagopal, Premkurmar; Tram , Nguyen Thi Thanh; Bardai , Barjoyai bin (Journal of Ecohumanism, 2024)
This study aims to examine the interrelationships among environmental strategy, environmental management accounting (EMA), environmental performance, and financial performance within manufacturing firms in Vietnam, a topic rarely addressed in previous research. Specifically, the research investigates the role of EMA use and environmental performance in mediating the relationship between environmental strategy and financial performance. Drawing on stakeholder theory, contingency theory, and the natural resource-based view theory, this study develops and tests a serial mediation model to explain how EMA use and environmental performance link environmental strategy to improved financial performance Data were collected from 198 manufacturing firms in Vietnam. The research employed partial least squares structural equation modeling (PLS-SEM) with SmartPLS software for data analysis. The findings reveal that environmental strategy positively influences both EMA use and environmental performance. Moreover, EMA and environmental performance act as significant mediators, positively influencing financial performance. This study focuses on manufacturing firms in Vietnam, an emerging market, which may limit the generalizability of the findings to other geographic contexts. Cultural differences, variations in environmental standards, and different levels of economic development across countries may influence the relationship between environmental strategies and performance outcomes, suggesting that the results may not be universally applicable. This research is the first to explore the interconnections between environmental strategy, EMA use, environmental performance, and financial performance in manufacturing firms in Vietnam. It provides valuable theoretical and practical insights for managers and policymakers, highlighting the importance of integrating environmental strategies into business operations.